UNRAVELING THE CONFLICT-RIDDEN WEAVE: THE REGIONAL SECURITY OF THE SAHEL REGION AMIDST WAGNER GROUP’S PRESENCE - Ramadhany, Ghifarie Aulia; Salahuddin Hakim, Mohammad Apridio; Manullang, Abel Josafat (UI Scholars Hub, 2024)
Mercenaries or guns for hire have been a considerable force to reckon with in the international system. Their involvement in the conflicts of all scales have their share of contribution to the eventual outcome of the conflict. Such is the case of the Wagner Group. As a non-state actor, the Wagner Group has engendered numerous tempests across the world, one of them is the Sahel region. Their presence in the Sahel region has been a focal point of disputes within the international community. Against that backdrop, the paper seeks to shed light on how the regional security complex of the Sahel region has been severely affected by non-state actors like the Wagner group. In carrying out the research undertaking, the writers employ the qualitative research method that entails the use of secondary data alike along with the regional security complex as the guiding theoretical framework. This paper lodges how the Sahel region regional security dynamic has been subjected to changes as a result of the Wagner group’s pursuit of their own set of interests. However, it is important how the leeway for them to do so was made available by the states who reside in the region.